Inovasi Nilai Dalam Langkah – Langkah Sistematis Blue Ocean Shift (Studi Kasus Pada Biznet Branch Sukabumi) - Muhammad Dirham; Erry Sunarya; Kokom Komariah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to explore the strategic concept carried out by Biznet based on the concept of value innovation in the systematic steps of Blue Ocean Shift in an effort to create value differentiation. The informants in this research are Biznet Managers as decision makers in the strategy and Biznet Customers as the object of determining the success of the strategy . This study uses a qualitative method with a case study approach. Data collection techniques using observation, interviews and documentation. Data analysis techniques through data reduction procedures, data presentation, and drawing or verifying conclusions. The data validity technique in this study uses source triangulation, technical triangulation, and time triangulation methods. The results show that Biznet has done the right thing in increasing its potential as an opportunity to develop its products into value innovations, namely the "The New Biznet Fiber Network" network. " which provides more quality / value to the customer. This can be seen from the process of each systematic step that has been carried out in this research. Thus, this research is expected to provide complete and comprehensive insight regarding the implementation of the Blue Ocean Strategy in the Internet Provider Industry for Biznet's management in determining the strategic direction in the future. Keywords: Value Innovation, Blue Ocean Shift, Internet Provider